Epistemic Trust, Mistrust and Credulity Questionnaire (ETMCQ) validation in French language: Exploring links to loneliness. - Christian Greiner; Vincent Besch; Marissa Bouchard-Boivin; Catherine Le Hénaff; Cécilia Von Rohr-De Pree; Nader Perroud; Paco Prada; Martin Debbané (PLoS ONE)
The concept of epistemic trust is gaining traction in the mental health field. Epistemic trust is thought to play a foundational role as a resilience factor against the development and maintenance of psychopathology by fostering social learning. The primary aim of this study was to validate the French-language version of the Epistemic Trust, Mistrust and Credulity Questionnaire (ETMCQ). We further sought to replicate previously reported associations with key developmental and psychological factors (childhood trauma, mentalizing and attachment) and test for epistemic trust's potential mediating roles between childhood traumatic experiences and psychopathology, and between loneliness and psychopathology. A total of 302 participants were recruited via the online survey platform Prolific. Confirmatory factor analysis and generalized linear models of mediation were conducted. Our findings suggest that the ETMCQ is a valid instrument to assess epistemic trust in the French language. Satisfactory psychometric properties were found to replicate the original three-factor solution in a Francophone population with a 12-item version of the questionnaire, with criterion-related validity similar to that previously published in validations of the ETMCQ in other languages. We also replicate previous findings reporting differential associations between epistemic stances (trust, mistrust and credulity) and attachment dimensions and styles, while also replicating mediation analyses showing the role of epistemic stances in the relationship between childhood traumatic experiences and psychopathology. Finally, we report preliminary evidence suggesting that epistemic trust mediates the well-described association between loneliness and psychopathology. Future research should investigate the ETMCQ in clinical populations in which psychopathological expressions are severe, enduring and co-occurring, where identifying potential mediators could help target and personalize psychosocial interventions.